The New Testament doctrine of the Christ;: the Bampton lectures for 1926 - Rawlinson, A. E. J. (Bampton lectures 1926, 1926)
The Jewish religious hope -- The Christology of the Jewish-Christian Church -- The gentile-Christian mission -- The contribution of S. Paul--I -- The contribution of S. Paul--II -- The contribution of S. Paul--III -- Mediator, high priest, living one -- The incarnation of the Word -- Appended notes. The title 'Lord' in pre-Hellenic Christianity ; The designations 'servant' as applied to our Lord ; On the meaning and use of the title 'Son of Man' in the Gospels ; The 'filial consciousness' of Jesus ; On the alleged 'adoptionism' of primitive Christianity ; Christianity and the 'mystery religions'